2013
DOI: 10.3109/10520295.2013.832798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of double ligation of Stensen's duct on the rabbit parotid gland

Abstract: Salivary gland duct ligation is an alternative to gland excision for treating sialorrhea or reducing salivary gland size prior to tumor excision. Duct ligation also is used as an approach to study salivary gland aging, regeneration, radiotherapy, sialolithiasis and sialadenitis. Reports conflict about the contribution of each salivary cell population to gland size reduction after ductal ligation. Certain cell populations, especially acini, reportedly undergo atrophy, apoptosis and proliferation during reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Maria et al (2013) reported that double ligation of Stenson’s duct of the rabbit parotid gland led to a sequence of inflammation of the lobules, atrophy and apoptosis of acinar cells, and cell proliferation which occurred almost exclusively in the largest excretory ducts. These changes were the result of the build-up of back pressure caused by the double ligation of the duct, which led to an accumulation of secretory material in dilated ducts and acini.…”
Section: Discussionmentioning
confidence: 99%
“…Maria et al (2013) reported that double ligation of Stenson’s duct of the rabbit parotid gland led to a sequence of inflammation of the lobules, atrophy and apoptosis of acinar cells, and cell proliferation which occurred almost exclusively in the largest excretory ducts. These changes were the result of the build-up of back pressure caused by the double ligation of the duct, which led to an accumulation of secretory material in dilated ducts and acini.…”
Section: Discussionmentioning
confidence: 99%
“…The reported frequency of salivary cell proliferation in animal studies varied from as low as 0.3–1.5% to as high as 60–70%. These results may be due to different methods, species, parenchymal cell type, distribution, gender, and the age of sacrifice of the experimental animals (Chai et al , ; Denny et al , , ; Redman, ; Maria et al , ; Aure et al , ). Redman et al (Redman, ) reported that the thymidine‐labeled cell rate in parotids was ~15% in 1‐ to 3‐week‐old rats and ~5% after 4 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
“…Frequently, the areas of mixed serous and ductal cells were visualized as illustrated in Figure 4B . Acini also have been reported to de-differentiate into ducts 15 . Ihrler, et al 13 (2002) demonstrated that evidence of a mixed phenotype suggests the transition and differentiation of cells through metaplasia.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the number of DLS allows speculation that a mitotic process is occurring within the cells or even a transition of an acinus to a duct 15 , 28 because the acini disappear while the DLS increase in number. The true origin and the phenotype of the DLS are not known.…”
Section: Introductionmentioning
confidence: 99%